Upaya Meningkatkan Sikap Kepemimpinan Pengurus Osis Melalui Sosiodrama - Apriani, Muthmainnah (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2014)
The attitude of the leadership of the most prominent school environment that is at OSIS which has a role in promoting the school, but the school also sometimes just pay attention to students who have shown ability to lead but did not give a chance to the other students. The purpose of this study was to determine the increase leadership attitudes through sociodramas OSIS SMAN 1 Poor Bantul Yogyakarta. This research is a class action (classroom action research) using sociodramas. Subjects in this study were 14 students OSIS. The data collection is done by using a questionnaire instrument leadership attitudes, and the observation sheet. The validity of research instruments using internal validity with item analysis using product moment formula, while for the reliability test using internal reliability with alpha formula. Analysis of the data in this study using the formula t-test to see the difference in the mean pretest and posttest results. The results of this research note that the method sociodrama can improve the attitude of the leadership, it is based on the pretest are in enough category by the number of frequency of 14 to 100%, and at posttest are in enough category with a number of frequency 8 at 57.14%, and then in the category both the number of frequencies 6 by 42.86%, so it can be concluded that there is an increasing position of leadership through sociodrama OSIS SMAN 1 Poor Bantul Yogyakarta. The results of this study can be useful for guidance and counseling teachers in developing guidance service groups using sociodrama to support student leadership attitude. For Deputy Head of Student and Pembina OSIS, this study may provide information about students attitudes OSIS leadership so that it can be used as a reference in making the right program for OSIS.